Efficacy of Shexiang Tongxin Dropping Pills in a Swine Model of Coronary Slow Flow - Bai, Yupeng; Zhang, Mingjing; Peng, Sheng; Wang, Yuting; Gu, Ye; Fang, Qianqian; Hu, Liqun (Frontiers in Physiology, 2022)
Objective:Preliminary clinical studies confirmed that Shexiang Tongxin dropping pill(STDP) could improve angina pectoris and attenuate vascular endothelial dysfunction in patients with slow coronary flow,but the underlying mechanism is not fully unclear.We aimed to investigate the impact of STDP in a swine model of coronary slow flow (SF) and related mechanism.Methods:SF was induced by coronary injection of 40𝜇m microspheres, pigs were randomly divided into SF group and SF plus STDP group. Pigs in STDP group received sublingual STDP for 10 minutes, followed by 1 gram STDP oral administration daily for 6 days. Coronary angiography was performed and TIMI frame count (TFC) was determined and hemodynamic measurements were performed before, at 30min and 7 days post SF. Serum levels of total NO, NOS, ET-1,C-TNI and BNP were measured. Myocardial expressions of TNF and IL-6, eNOS, VEGF, CD31 and α-SMA were analyzed by immunohistochemistry and Western blotting. Results:Compared to SF group, LVEF and TFC were significantly improved at 7 days post SF in STDP group. Serum ET-1 level was significantly reduced at 7 days, NO and NOS levels were significantly higher in STDP group. Seven days post SF, myocardial TNF and IL-6 expression were significantly downregulated, while the expressions of eNOS and VEGF, CD31 and ɑ-SMA were significantly upregulated in STDP group. Conclusion:Our results showed that STDP improved cardiac function and coronary flow, possibly through reducing inflammatory responses and upregulating myocardial eNOS and VEGF, CD31 and ɑ-SMA expression.